Bachelor of Commerce Programme and employability of University of Venda graduates, South Africa - Oseifuah, Emmanuel K.; ., George NovisiKwadzo; ., Vukor-Quarshie (Journal of Economics and Behavioral Studies, 2014)
Since its establishment two and half decades ago, the School of Management Sciences at the University of Venda (UNIVEN) has produced hundreds of Bachelor of Commerce (BCOM) graduates for the South African work force. Yet the School has had no formal feedback from its graduates regarding the relevance, usefulness, strengths and weakness of its BCOM programmes. The purpose of this study was to assess the impact of the BCOM (Accounting) programme on job prospects of UNIVEN graduates. A structured questionnaire was sent to a sample of 61 graduates of UNIVEN’s BCOMA programme through the Snowball technique of tracing survey respondents. The questionnaire sought the participating graduates’ opinions on several aspects of their educational experience at Univen including adequacy of the training and employability, among others. The study used the IBM SPSS version 21 to analyse the study data. The key findings of the study suggest that the components of the BCOMA programme that need major improvement to increase the employability of graduates are training in practical skills, using computers in Accounting training, as well as improvement in teaching and delivery methods. The study also found that modules offered in the BCOM programme were relevant to the graduate’s job needs.